PENGARUH RELATIONSHIP MARKETING TERHADAP LOYALITAS NASABAH DI PT.BANK MANDIRI KC.DOTULOLONG LASUT MANADO - KANDOU, HAJAR ASWAT; KALANGI, Johny A. F.; ROGAHANG, JOULA J. (Sam Ratulangi University, 2017)
At Bank Mandiri KC.Dululolong Lasut Manado experienced theproblem of unstable customer savings rate. This unstable number of subscribersis biased by the downturn in the client's economic condition, or there are otherfactors between services that do not correspond to unsatisfactory interests orunsatisfactory facilities that customers turn to other banks. Planting thecredibility of the company, certainly not an easy thing, it takes an appropriatestrategy for the purpose and objectives can be achieved optimally, especially inthe field of marketing. Basically Relationship marketing is a long-termrelationship and bond between producers, consumers, suppliers, and otheractors. Customer loyalty is a behavior associated with a product's brand,including possible renewal of a contract in the future. This research usesquantitative method, sampling technique in this study using Simple RandomSampling, The formula used in calculating this simple correlation coefficient isproduct moment. From the results of statistical testing can be seen clearly thatthe free variable Relationship Marketing affect the dependent variableCustomer Loyalty. the influence of the given free variable is positive whichmeans the more active relationship marketing then result in higher loyalty ofcustomers generated. These results are also in accordance with the proposedhypothesis. This shows that relationship marketing is one of the determinants ofcustomer loyalty because good relationship marketing will create and maintaincustomer loyalty. So the higher the relationship marketing applied will increasecustomer loyaltyKeywords: Relationship Marketing and Customer Loyalty